Mutations matter: An observational study of the prognostic and predictive value of KRAS mutations in metastatic colorectal cancer - Lavacchi, Daniele; Fancelli, Sara; Roviello, Giandomenico; Castiglione, Francesca; Caliman, Enrico; Rossi, Gemma; Venturini, Jacopo; Pellegrini, Elisa; Brugia, Marco; Vannini, Agnese; Bartoli, Caterina; Cianchi, Fabio; et al. (Frontiers in Oncology, 2022)
Background About half of metastatic colorectal cancers (CRCs) harbor Rat Sarcoma (RAS) activating mutations as oncogenic driver, but the prognostic role of RAS mutations is not fully elucidated. Interestingly, specific hotspot mutations have been identified as potential candidates for novel targeted therapies in several malignancies as per G12C. This study aims at evaluating the association between KRAS hotspot mutations and patient characteristics, prognosis and response to antiangiogenic drugs. Methods Data from RAS-mutated CRC patients referred to Careggi University Hospital, between January 2017 and April 2022 were retrospectively and prospectively collected. Tumor samples were assessed for RAS mutation status using MALDI-TOF Mass Spectrometry, Myriapod NGS-56G Onco Panel, or Myriapod NGS Cancer Panel DNA. Results Among 1047 patients with available RAS mutational status, 183 KRAS-mutated patients with advanced CRC had adequate data for clinicopathological and survival analysis. KRAS mutations occurred at codon 12 in 67.2% of cases, codon 13 in 23.5%, codon 61 in 2.2%, and other codons in 8.2%. G12C mutation was identified in 7.1% of patients and exon 4 mutations in 7.1%. KRAS G12D mutation, as compared to other mutations, was significantly associated with liver metastases (1-sided p=0.005) and male sex (1-sided p=0.039), KRAS G12C mutation with peritoneal metastases (1-sided p=0.035), KRAS G12V mutation with female sex (1-sided p=0.025) and no surgery for primary tumor (1-sided p=0.005). No associations were observed between specific KRAS variants and age, ECOG PS, site of primary tumor, pattern of recurrence for resected patients, and lung, distant lymph node, bone, or brain metastases. Overall survival (OS) was significantly longer in patients with KRAS exon 4 mutations than in those with other KRAS mutations (mOS 43.6 months vs 20.6 months; HR 0.45 [0.21-0.99], p=0.04). No difference in survival was observed for mutations at codon 12/13/61 (p=0.1). Treatment with bevacizumab (BV) increased significatively mPFS (p=0.036) and mOS (p=0.019) of the entire population with a substantial benefit in mOS for G12V mutation (p=0.031). Conclusions Patterns of presentation and prognosis among patients with specific RAS hotspot mutations deserve to be extensively studied in large datasets, with a specific attention to the uncommon isoforms and the role of anti-angiogenic drugs.